Quality of life in a family-centric applied behavior analysis model: A case series study - Madalina Ciobanu; Gina Barnes; Natalie J. Castell; Robert P. Adelson; Anurag Garikipati; Navan Preet Singh; Qingqing Mao; Ritankar Das (PLoS ONE, 2025)
Autism spectrum disorder (ASD) is a condition with growing prevalence that results in significant healthcare spending, reduced parent income, high levels of family stress, and decreased quality of life (QoL). QoL is a measure for assessing overall wellness, and in the context of ASD is related to parent self-efficacy. Validated treatments, of which applied behavior analysis (ABA) is the gold standard, can mitigate some of the consequences that may be detrimental to parental QoL. We examined changes in parental QoL across multiple domains within three parent-child dyads in the context of a parent-led ABA model where the treatment was delivered by the parent. We hypothesized that parental QoL would be increased concurrently with ABA treatment lowering the frequency of interfering behaviors, which contribute to parental stress and limited self-efficacy. QoL components improved between the first and follow-up evaluations, though not all QoL component score changes achieved clinical significance. This study demonstrates a correlation between parental QoL and clinical treatment progress; with further validation, QoL assessment may serve as a tool to guide individualized treatment approaches that improve family outcomes.